Employees in Asian Enterprises: Their Potential Role in Corporate Governance - Sang-woo Nam (Asian Development Bank Institute (ADBI), 2003)
Employees with valuable human capital are becoming the most essential asset in the era of global competition, and a great challenge for corporate governance is how to motivate them. Employees will increasingly be induced to participate in shop floor decision-making. This will gradually allow them to participate in corporate governance as well. While works councils are likely to be the most promising channel for employee participation in corporate governance, also important are such complements as employee stock ownership and conducive work organization and human resource management.
hdl:11540/4157
Keywords: 330